The Effect of Customer Personality and Customer Experience on Zara Consumer Satisfaction in Malang City: Consumer Satisfaction in Malang City - Ma'rifatul Mukhlisoh; Aninda Sinta D; Ariel Jimy F; Muhsin Muhsin; Azizah Dwi Safira; Paul Teller (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The aim of this study is to examine how customer satisfaction with Zara products in Malang is influenced by customer experience and personality. This study employs a cross-sectional design and an explanatory quantitative methodology. Sampling was carried out using a purposive approach, and the study population comprised all Zara customers in Malang who had previously made a purchase. A five-point Likert scale questionnaire and documentation were used to collect data. The analytical methods employed included validity and reliability testing, testing of traditional assumptions, and multiple linear regression analysis with partial t-tests and simultaneous F-tests. The results indicate that customer satisfaction is positively and significantly influenced by customer personality (t-value = 4.312; p = 0.000). Furthermore, customer satisfaction is also positively and significantly influenced by customer experience (t-value = 5.127; p = 0.000). When considered together, these two factors have a significant impact on customer satisfaction (F-value = 38.214; p = 0.000), with a coefficient of determination (R²) of 0.634. It has been demonstrated that a positive shopping experience, combined with a good fit between customer personality and the Zara brand image, enhances customer satisfaction. Keywords: customer personality, customer experience, consumer satisfaction, Zara, Malang City